Calcium and the Fc Receptor on Human Platelets - Clark, William F; Tevaarwerk, Gerald J M; Reid, Bruce D; Hall, Suzanne; Caveney, Anita; Parbtani, Anwar; Kreeft, John (Thrombosis and Haemostasis, 1987)
We have described the calcium dependence of the IgG Fc receptor (Fc-R) on human platelets by analyzing the direct binding of radiolabelled Fc fragments, monomers and dimers of IgG. Specific binding to platelets was undetectable at 37° C in a calcium-free preparation but readily detected when calcium was restored. Scatchard analysis of the binding data for the calcium-restored platelets permitted calculation of the available Fc-R and the Ka of binding for the different IgG ligands. The mean Ka of binding for 12 normal subjects varied from 107 to 108 L/M, with an equal receptor number measured by Fc fragments and dimers of IgG, but a lesser amount for monomeric IgG. There was no apparent difference in Fc-R number for platelets from 6 normal male versus 6 normal female subjects.At 4° C binding was detectable for dimers and polymers of IgG in a calcium-free preparation and this was markedly increased with recalcification. Thus, our data are consistent with an Fc receptor population on human platelets whose avidity for binding is significantly enhanced in a calcium-restored medium.
Keywords: Platelets; Fc receptor; Calcium; IgG; Fc fragments